High Density Lipoprotein Cholesterol (HDL-C) Status in Patient’s of Acute ST–Elevation Myocardial Infarction (STEMI) - Uddin, Mohammad Kafil; Ahmed, Farhena; Hossain, Md Kamal; Khatun, Monira; Meah, Mohammad Musa (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background : Decrease plasma High Density Lipoprotein Cholesterol (HDL-C) and increase triglyceride are major dyslipidemia in our country due to effects of carbohydrate rich diet. The relationship of low level of HDL –C in patient’s of AMI and its extents of severity in coronary artery disease will be very important for future management as well as prevention of Coronary Artery Disease (CAD). Objective : The aim of this study is to assess the level of serum HDL-C in AMI patient and to assess whether low serum HDL-C level is an independent risk factor for acute ST elevation MI. Methods : It is a hospital based cross sectional observational study. 280 patients of acute STEMI who are admitted in coronary care unit selected for study. After estimation of serum lipid profile of these patients their serum level of HDL-C were used to detect the relationship between serum HDL-C and acute ST elevation MI. Results : In our study, among the case group (280 patiens) lipid profile estimation showed that about 64% patients of acute STEMI have low level of serum HDL-C. The other lipid fractions like triglyceride, low density lipoprotein cholesterol as well as total cholesterol were high in about 24%,39% & 44% but normal in 76%, 61% & 56% respectively. Conclusion : There is an independent inverse association of serum HDL-C in patients of acute STEMI and its an important indepedent risk factor. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 11-14